Evaluation of BUMDesa Performance on Village Economy in Bengkalis Regency - Muttaqin, Husnul; Sukma, Doris; Astari, Yanisha Dwi; Dalimunthe, Deliana (ABEC Indonesia, 2024)
This research aims to evaluate the performance of Village-Owned Enterprises (BUMDesa) on the villageeconomy in Bengkalis Regency. The focus of this research was conducted on two independent BUMDesa, namelyBUMDesa in Kuala Alam Village and Jangkang Village. The research approach used was descriptive qualitative method,where data was collected through in-depth interviews, field observations, and document studies. The analysis in thisstudy aims to describe how BUMDesa contribute to improving the village economy through job creation, increasingcommunity income, as well as local business development. The results show that BUMDesa in both villages studied havea good impact in driving the village economy. In Kuala Alam Village, BUMDesa Kuala Alam plays an active role in thetrade, seafood and plantation sectors, which directly increases the income of the local community. While in JangkangVillage, BUMDesa Sejahtera focuses on the trade and drinking water processing sectors, which also contributes well tothe village economy. However, this research also found several obstacles faced by BUMDesa, particularly in terms ofbusiness management, human resource management. From these findings, it is recommended to increase managerialtraining for BUMDesa administrators, human resource capacity building, and increase synergy between BUMDesa andlocal government to improve the effectiveness and sustainability of BUMDesa programs in supporting village economicdevelopment.